Arab TV-audiences: negotiating religion and identity - Galal, Ehab (PL Acad. Research, 2014)
Where has the authority gone? : new imperatives and audience research / Ehab Galal -- Audience responses to Islamic TV : between resistance and piety / Ehab Galal -- Cyber religious-national community? : the case of Arab community in Germany / Khalil Rinnawi -- Maghrebi audiences : mapping the divide between Arab sentiment, Islamic belonging and political praxis / Ratiba Hadj-Moussa -- Religious media as a cultural discourse : the views of Arab diaspora in London / Noha Mellor -- Watching the history of the "present" : religion and national identity in the Egyptian diaspora / Vivian Ibrahim -- Minority religion mediated : contesting representation / Lise Paulsen Galal -- About the contributors